(untitled) (The Review of Diabetic Studies, 2024)
Background: Evidence-based practice (EBP) remains the cornerstone of high-quality, safe, and cost-effective healthcare. However, gaps between research and clinical implementation persist, especially in regions with limited nursing research infrastructure. Strengthening nursing research and innovation is crucial to bridge these gaps and enhance patient outcomes. Aim: This review examined recent literature (2020–2024) to explore how initiatives promoting nursing research and innovation influence EBP and healthcare outcomes. Method: A systematic search across PubMed, CINAHL, Scopus, Web of Science, and Google Scholar yielded 476 records. Following screening and de-duplication, ten studies met inclusion criteria. Data were extracted on study design, context, interventions, and outcomes, and appraised using a literature quality matrix. Results: The studies included qualitative, cross-sectional, and review designs. Major themes were: fostering a research-oriented culture, education and training, technological innovation, organizational leadership, and integration of research into practice through learning health systems. Findings showed that nurses’ knowledge, training, and supportive work environments strongly influence EBP readiness, while inadequate resources and leadership hinder implementation. Learning health systems effectively embed research into care processes, reducing the evidence-to-practice gap. Overall, EBP adoption improved patient safety, care quality, and professional development. Conclusion: Promoting nursing research and innovation strengthens EBP uptake and optimizes patient outcomes. Key strategies include establishing research priorities, enhancing education and mentorship, fostering supportive organizational cultures, leveraging technology, and embedding learning health system models. Policymakers should champion nurse-led research to achieve sustainable healthcare improvements.